Transcending Borders: Arabs, Politics, Trade, and Islam in Southeast Asia by Huub de Jonge and Nico Kaptein, eds. (Leiden: KITLV Press, 2002. 246 pages.) (American Journal of Islam and Society, 2005)
This collection of essays is a spin-off of a workshop held in December1997, which was jointly organized by the venerable Koninklijk Instituutvoor Taal-, Land- en Volkenkunde (the Royal Institute of Linguistics andAnthropology) and the more recently established International Institute ofAsian Studies in Leiden, the Netherlands. Both are important resource centersfor the study of Islam in Southeast Asia and are closely connected withLeiden University, which has a formidable reputation as a centuries-oldcenter of learning in Islamic and Asian studies. Publications like the presentone show that academic institutions with roots in the colonial past andwhich were once part of the now much-criticized scholarly tradition of“Orientalism” can reinvent themselves and continue to make valuable contributionsto the study of non-western cultures.Transcending Borders focuses on the phenomenon of Arab settlementin Southeast Asia. Although the role of these migrants in the Islamizationof the Malay–Indonesian archipelago has long been acknowledged, questionspertaining to their integration into Southeast Asian society and theresulting impact on their ethnic identity have received far less attention. Infact, the upsurge in research into these aspects is barely a decade old.However, the most recent developments in Muslim Southeast Asia will certainlykeep that interest alive, because some of the more militant key playersin Southeast Asian Islamic revivalism are themselves of Hadrami orsouthern Arabian descent.The book’s 10 articles approach the study of Arab migration and settlementfrom historical, sociological, anthropological, and Islamologicalperspectives. However, the editors have taken care to ensure that these differentapproaches provide intersecting images of the Arab presence in ...